Bronchoscopy in intensive care: to whom, when, why? (literature review) - O.Yu. Usenko; A.V. Sydiuk; O.Ye. Sydiuk; V.V. Antonenko; S.I. Chechil (Медицина неотложных состояний, 2025)
Bronchoscopy is a fundamental tool in the armamentarium of an intensivist. This procedure is useful in the diagnosis and management of acute respiratory failure. It can be rapidly implemented at any time at the bedside and requires minimal assistance to perform. Bronchoscopy has become a standard of care for the triad of inspection, sampling, and treatment in critical care patients. It is an invaluable tool for diagnostic and therapeutic purposes in critically ill patients in intensive care unit. This article covers various important aspects, including patient selection and preparation, diagnostic bronchoscopic procedures, equipment disinfection, and bronchoscopy in critical care setting.